Nanomaterials for application in medicine and biology - Giersig, Michael. (Springer, 2017)
This volume contains research reports presented during the NATO Advanced Research Workshop (ARW) "e;Materials for Application in Medicine and Biology"e; held in Bonn, Germany, from October 4 to 6, 2006 at the center of advanced european studies and research (caesar). The application of nanomaterials in medicine and biology can be understood as the gathering and use of our current knowledge on nanoscale features of b- logical systems in order to learn how to design nanodevices for biomedical uses. The success of this approach, known as nano-engineering, will allow scientists to devise strategies for the design and construction of nanodevices to be used in clinical trials (diagnosis and therapeutic monitoring), as well as to develop products with potential applications in regenerative medicine. One goal of this conference was to bring together researchers from Eastern and Western countries, offering them a platform to meet and discuss results of their research work. Thus, the aim of this conference was not only to present the advancements in research achieved during the past years, but it had also been conceived as a concerted European effort where expertise, technologies, and ideas were broadly shared to accelerate this progress. The conference provided an interactive forum with more than 100 participants from 15 countries.